Role of Zinc Supplementation in the Treatment of Levetiracetam-Induced Hair Loss: A Case Series - Vajiheh Aghamollaii; Zahra Ghelich Khan; Andisheh Maneshi; Padideh Ghaeli (Research Center for Rational Use of Drugs (RCRUD), 2017)
Objective: Cosmetic side effects are of important causes for non-compliance in patients on anti-epileptics. TE is among the most encountered cosmetic adverse effects. Method: This report presents three patients with seizure disorder who developed levetiracetam- induced TE. Levetiracetam was considered the best therapeutic option for the treatment of the presented patients and therefore, was not changed to other anti-epileptics. To manage TE, it was decided to add Zinc sulfate to the therapeutic levetiracetam regimen. Results:  All three patients reported improvement in their hair condition while their seizure was controlled. Significance: Levetiracetam has favorable safety and efficacy profiles. However; the hair loss caused by this medication is a major drawback. Zinc supplementation is suggested to be safe and cost effective when considering management of levetiracetam-induced TE.